WTO dispute settlement procedures : a collection of the legal texts - Marceau, Gabrielle (World Trade Organization GenevaCH, 1995)
Contains a collection of the legal texts related to the settlemet of disputes under the GATT 1947 and the Agreement Establishing the World Trade Organization.